Mental health issues in the schools: are educators prepared?. Issue 4 (2nd December 2014) - Andrews, Amy; McCabe, Mike; Wideman-Johnston, Taunya
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Mental health issues are exceedingly prevalent in society. Approximately one in five people will experience a mental illness within their lifetime and serious mental illnesses are most likely to emerge between the ages of 16 and 24. This research endeavored to gain a better understanding of teachers' knowledge and perceived roles in dealing with students with mental health issues. The purpose of this paper is to explore teacher education programs and other resources accessible to teachers as well as barriers to their continued learning about issues related to mental health. Design/methodology/approach – In total, 75 secondary school teachers completed an online survey consisting of 42 Likert-style questions constructed with the main objective of the study in mind. The questions were organized under five different subheadings in the survey in order to provide some direction regarding the research questions. Measures of central tendency were utilized to determine frequencies of responses. The researchers created summary tables of the data for analysis purposes. Findings – Teachers indicate that it is within their role to deal with mental health issues, but many do not have the knowledge to do so. Teacher education programs are not providing enough preparation for teachers and, although available, many teachers do not have knowledge of resources produced by interest groups. Research limitations/implications – Teacher education programs, both pre-service and in-sevice, must respond to the needs of teachers. In doing so, the authors can then address the needs of students and assist them in the challenges that mental illnesses present. Practical implications – While an educator's role does not officially include being a mental health practitioner, it is their role to educate all students. This inevitably requires an understanding of the connection between mental health issues and how they affect a student's ability to learn and to live a healthy life. Social implications – Resiliency theory suggests "the most important and consistent protective factor is that of adults caring for children during or after major stressors" (Masten et al., 1991, p. 431). Who better placed to assist them than teachers? Originality/value – This research adds to the ever-increasingly difficulty tasks that teachers are charged with implementing. It identifies a clear need for increased attention to preparing teachers.